Contacting BBr3-based Boron Emitters with Aluminium-free Screen-printing Paste. (August 2016) - Fritz, Susanne; Emre, Erkan; Engelhardt, Josh; Ebert, Stefanie; Nowak, Nicolas; Booth, Jonathan; Hahn, Giso
Abstract: For n-type solar cell concepts, B emitters are commonly diffused in a BBr3 -based process. However, the metallization of these p + layers is challenging. Up to now, low contact resistances on B emitters were only reported to be possible using Al-containing Ag screen-printing pastes. A drawback of the addition of Al to the paste is that, facilitated by the Al, deep metal spikes grow into the Si surface. As these spikes are deep enough to penetrate the emitter and affect the space charge region, they are made responsible for low Voc values that limit solar cell efficiency. However, in 2015 Engelhardt et al . reported specific contact resistances around 1 mΩcm 2 of Al-free Ag screen-printed contacts on B emitters diffused by inductively coupled plasma plasma enhanced chemical vapour deposited SiOx :B layers. In their process the doping layer remained on the wafer serving as surface passivation layer. The low contact resistances were attributed to the presence of the doping layer. In this work we use two Al-free Ag screen-printing pastes for contacting a BBr3 -based B emitter. Specific contact resistances well below 10 mΩcm 2 are reached on alkaline textured wafers with dielectric layer. It is shown that with the use of Al-free Ag screen-printing pastes deep spiking can be avoided and therefore a wider window of firing parameters is available. These results allow the use of the same screen-printing paste on both sides of the solar cell. Additionally it is shown, that with an old generation Al-free Ag paste low specific contact resistances can only be achieved in a narrow firing window at low temperatures. The addition of Te to the old generation paste shifts and broadens the temperature range for which low specific contact resistances are reached to higher firing temperatures.